Laparoscopic gastrostomy in a patient with asphyxiating thoracic dystrophy - Ediana Hoxhallari; Elliot C. Pennington (Elsevier, 2022)
Introduction: Asphyxiating thoracic dystrophy (ATD), also known as Jeune syndrome, is an autosomal recessive disease which causes thoracic insufficiency. Complications and life expectancy vary based on specific mutations. Infants with this condition may require operative feeding access in addition to surgery for other associated anomalies. No prior cases of laparoscopic surgery in ATD have been recorded in the literature. This case demonstrates that with proper technique, laparoscopic surgery can be accomplished safely. Case presentation: Newborn diagnosed with ATD prenatally with anatomical 20-week ultrasound who required long term enteral feeding access due to inability to tolerate oral feeds secondary to tachypnea. Management and outcome: Patient underwent laparoscopic gastrostomy tube placement at 2 weeks of age. This was well tolerated, and no complications arose from insufflation pressure despite small thoracic volumes. Pressure control ventilation was used along with frequent desufflation breaks. Patient tolerated tube feeds at goal until expiration at 8 weeks of age. Discussion: Laparoscopic surgery can be safely performed in patients with ATD with appropriate monitoring and ventilatory support. Although ATD is commonly fatal, this type of palliative surgery can improve patients' quality of life and allow them to discharge home safely so they can spend more time with family.